2017
DOI: 10.1007/s40192-017-0100-9
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Assays for Additively Manufactured Ti-Ni Alloys Based on Compositional Gradients and Spherical Indentation

Abstract: Recent advances in additive manufacturing (AM) reveal an exciting opportunity to build materials with novel internal structures combined with intricate part geometries that cannot be achieved by traditional manufacturing approaches. The large space of potential material chemistries combined with non-equilibrium microstructures obtained in AM presents a significant challenge for a systematic exploration and optimization of the final properties exhibited by AM parts when using the existing knowledge databases es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…As demonstrated in previous studies [ 37 , 39 , 82 , 105 ], the averaged values from the multiple indentations summarized in Figure 7 provide reliable measures of the bulk properties measured in standardized tests. The estimated Young’s moduli did not show clearly identified trends between the different material conditions explored in this study, and fell in the range of 97–130 GPa.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As demonstrated in previous studies [ 37 , 39 , 82 , 105 ], the averaged values from the multiple indentations summarized in Figure 7 provide reliable measures of the bulk properties measured in standardized tests. The estimated Young’s moduli did not show clearly identified trends between the different material conditions explored in this study, and fell in the range of 97–130 GPa.…”
Section: Discussionsupporting
confidence: 65%
“…In recent work [ 37 ], it was demonstrated that it is possible to prototype compositionally graded AM samples and characterize their mechanical properties using the stress–strain analysis protocols based on spherical indentation. This strategy appears to exhibit tremendous potential for the high-throughput extraction of the relationships between the processing conditions, microstructural features and properties [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The deviation from a nominally equiaxed alpha particle ( Figure 5(c)) present in the parent material to the deformed particles present in the TMAZ (Figure 5(b)) can be quantified by measuring the eccentricity of the grains which ranges from 0 for a perfect circle to 1 for a straight line, [22] which was automatically measured using a software package (MIPARä). [23] The undeformed a particles shown in Figure 5(c) had an eccentricity value of 0.49, while the plastically deformed alpha particles had an eccentricity value of 0.97. These quantitative measurements of eccentricity can be easily correlated with the elastic strain by considering these particles to be oblates .…”
Section: Resultsmentioning
confidence: 97%
“…AM offers the research advantage of produce graded compositions within the same sample. This is achieved by using elemental powder blends in a system with multiple hoppers (Collins [2003] and Gong et al [2017]).…”
Section: Additive Manufacturingmentioning
confidence: 99%